PEER RELATION SEBAGAI PREDIKTOR UTAMA SCHOOL WELL-BEING SISWA SEKOLAH DASAR - Wijayanti, Puspita Adhi Kusuma; Sulistiobudi, Rezki Ashriyana (Jurnal Psikologi, 2018)
Measuring school well-being in elementary school student is important. The experience of students at school will affect their perception, motivation and hope for their academic life in the future. We used Tripartite School Well-Being Model, based on the interaction among three aspects, namely school satisfaction, positive affect and negative affect. The aim of the study is to identify factors predicting the emergence of student’s positive affect and negative affect in elementary school. A total of 118 elementary school students of Class 6 in Bandung took a part in this study as respondent. The variables in this study were measured using three questionnaires: School Satisfaction, Positive Affect Student at School, and Negative Affect Student at School. Descriptive and inferential statistics through regression analysis was conducted to test the hypothesis. The results show that peer relationship, teacher-student relationship, and academic learning significantly contribute to build the positive affect of the student. Whereas, only the peer relationship predicted the negative affect of the student. This finding brings some practical implication for the educational process. The integrated multidimensional program which involves teacher, parents, peers, and student is crucial to promote student well-being at school.